Expansão da educação superior: um estudo da Universidade Tecnológica Federal do Paraná - Campo Mourão - Santos, Elton Moura (2016)
The proposal of developing this work arose from the inequalities resulting from professional work as social worker at the Federal University of Technology from Paraná Campus Campo Mourão (UTFPR-CM), wherewith was possible to keep up with implementation of the Program of Support for the Restructuring and Expansion of Federal Universities (REUNI), implanted the institution on the year of 2008. The REUNI, which compose the Education Policy of the Lula da Silva s government turned to the higher education, aimed enable the federal universities to increase the access and the permanence of students on the higher education, in order to improve the completion rates and increase the proportional ratio of students per university professors. Its implementation in the institution registered, in numbers, the University growth in several respects. However, this process occurred in a period in which, contradictorily, was registered the higher education enlargement on the sphere private, fueled by the enlargement of financing of public sources and having as principal instruments the Program of Financing Student (FIES) and the Program University for All (PROUNI), giving continuity to the precepts neoliberal that were in force on the government witch precede Lula da Silva and on it remained. The general objective of the study was analyze the repercussions of the expansion process of higher education, from the REUNI guidelines and from the legislations that follow it, under the UTFPR-CM. The research project counted with a judgment favorable from the Ethics Committee on the Unioeste research and the methodology adopted was the bibliography review and the documentary studies. In the first chapter, sought contextualize and understand the strategies of the capital in an attempt to get around the structural crisis installed since the decade of 1970, placing emphasis on neoliberal adjustments witch had as one of its deployment the against reform of the state. Was aborted this strategy, initially, more broadly and then contextualized on the Brazilian reality, placing emphasis on policies reformist implemented by the governments of FHC and Lula da Silva. In the second chapter we analyzed such policy reformist on the scope of educational policy implemented by the government Lula da Silva, taking into account the expansion of federal universities occurred in yours mandates (2003 to 2010). In the third chapter was settled the approach with the object of the search, that consists in investigate the elements witch compose the expansion process of the UTFPR, through the REUNI, seeking to do, firstly a contextualization socio-historical of institution development in overall and then of Campus Campo Mourão. With the data collect, it became possible demonstrate the implementation´s reflections from REUNI on the UTFPR-CM and, through qualitative analysis, demonstrate the contradictions present in this process, considering the political and economic moment from the development capitalist, when the expansion of the access to the high education at the federal universities was made in the middle of the privatization mechanisms growth of this level of education.